OPTIMASI NUMERIK STRUKTUR GONG UNTUK MEMPEROLEH RASIO FREKUENSI PRIBADI TERTENTU - Suweca, I Wayan; Cahyono, Eko (Mesin, 2006)
The sound quality of a gong is influenced by its dynamic characteristics (its structural eigenmode). By controlling natural frequency ratio of the gong to a certain value, we can expect to obtain the optimum gong design. The subject of the present research is to establish an analysis of the application of design optimization in obtaining an optimum gong design. The optimum gong is defined as a gong that has a certain natural frequency ratio. The natural frequency ratio adopted in this reseach is based on those of English bell [1]. The Sequential Unconstrained Minimization Techniques from Ansys 5.4 is used to perform the optimization process. The design optimization method has been successfully applied on the optimization of the gong. The results obtained from the three case studies show that the most sensitive part of the gong is at its around free end. This indicates that in manufacturing gong, this part must be carefully treated.